Functional constipation - Yu. O. Shulpekova; A. A. Kurbatova; A. V. Sedova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To discuss the recent updates in classification of constipation of functional origin (both as separate entity, and within the pattern of constipationpredominant irritable bowel syndrome), the concepts on pathogenesis and recommended treatment approaches. Key points. In 2016 multinational consensus statement on functional gastrointestinal disorders (so-called Rome IV criteria) was presented. In the section devoted to the bowel diseases the new entity - opioid-induced constipation was defined; besides that diagnostic (mostly - the time-based criteria) of irritable bowel syndrome and functional constipation were modified. In new Rome consensus different types of functional bowel diseases were considered as specific forms of certain continuum. The origin of functional bowel diseases is still presented in the context of biopsychosocial model; that develop due to impact of constitutive factors, in particular features of serotoninergic and adrenergic regulation, dietary habit, bile acid metabolism etc. In the recent years the role of intestinal microbiota changes was studied intensively. The treatment approach for functional constipation underwent no significant changes. First of all it is required to attempt to modify dietary habits and lifestyle, including consumption of fermented milk products; at the second stage food fibers are prescribed, at inefficiency of these measures - relatively safe laxatives, and if necessary - drugs to relieve pain. Administration of probiotics and prebiotics is the promising trend in the functional bowel disease treatment, being pathogenically justified and. Promising results are received at administration of specific strains of bifidobacteria and lactobacilli, in particular the combined probiotic «Florasan D» that includes Bifidobacterium bifidum, B.longum, B. infantis, Lactobacillus rhamnosus. Largescale studies proving efficacy of B. lactis DN-173 010 strain (the commercial name «ActiRegularis») at constipation and functional flatulence are received, the drug is included to the spectrum of functional nutritional products for daily intake.